2022
DOI: 10.3390/catal12070688
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Sulfate-Intercalated CoFe LDH Nanosheets Derived from Two-Dimensional ZIF-9(III) for Promoted Oxygen Evolution Reaction

Abstract: Layered double hydroxide (LDH) has emerged as a promising electrocatalyst; however, the synthetic method usually requires high temperature and high pressure, and sulfate-intercalated LDH is rarely reported. Herein, the sulfate-intercalated CoFe LDH nanosheets were successfully fabricated at ambient temperature via a facile strategy, using two-dimensional ZIF-9(III) as a template and FeSO4 as both etchant and iron source. When the as-prepared sulfate-intercalated CoFe LDH acts as an electrocatalyst, it presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…62 The increased activity could be due to the synergistic impact of Co and Fe, as well as the peculiar macropours architecture of the Co 4 Fe 6 -LDH catalysts. 63 Several investigations shown that Fe influences the regional electronic framework of Co–Fe materials, whereas CoOOH mostly served as a conductive and chemically stable host. According to Co 4 Fe 6 -LDH potential activity, 40 1.0 M KOH was in intimate contact with the dynamic region of the electrocatalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…62 The increased activity could be due to the synergistic impact of Co and Fe, as well as the peculiar macropours architecture of the Co 4 Fe 6 -LDH catalysts. 63 Several investigations shown that Fe influences the regional electronic framework of Co–Fe materials, whereas CoOOH mostly served as a conductive and chemically stable host. According to Co 4 Fe 6 -LDH potential activity, 40 1.0 M KOH was in intimate contact with the dynamic region of the electrocatalyst surface.…”
Section: Resultsmentioning
confidence: 99%
“…64,65 A weaker peak observed at 523 cm −1 is attributed to metal–oxygen vibrations observed for FeOOH 34,66 or the Co–O ( A g ) symmetric stretching mode, 52 and is consistent with the previous spectra for CoFe LDHs. 17,67…”
Section: Resultsmentioning
confidence: 99%
“…64,65 A weaker peak observed at 523 cm À1 is attributed to metal-oxygen vibrations observed for FeOOH 34,66 or the Co-O (A g ) symmetric stretching mode, 52 and is consistent with the previous spectra for CoFe LDHs. 17,67 No differences were apparent between the X-ray diffraction (XRD) patterns of the samples from either synthesis method as well (Fig. S4.6, ESI †).…”
Section: Characterisation Of the Optimized Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…S4 (ESI†) owned two typical M-O peaks at 490.9 cm −1 and 574.8 cm −1 , which is consistent with the results of FTIR. 16,17 The Raman peaks of the samples after the HER and OER were located at a fairly similar wavenumber to the original one. For the blunter peaks of CoFe-ZLDH/Ru@NF after the HER, it can be attributed to the decrease of the grain size.…”
mentioning
confidence: 80%